QUALITY ANALYSIS AND FORMALIN IDENTIFICATION OF SALTED FISH AT THE PASAR PAGI PEMALANG, CENTRAL JAVA - Afifah, Rufnia Ayu; Sayuti, Mohammad; Nur, Shinta Dia (Aurelia Journal, 2025)
Salted fish is one of the popular fish processing products in Indonesia. Even popular, currently, many salted fish containing formalin are found on the market. Consumption of salted fish with formalin poses serious health risks to humans. This study aimed to analyze the quality of salted fish and identify the presence of formalin in salted fish sold at the Pemalang Morning Market, Central Java. A total of 12 types of salted fish were identified at the Pemalang Morning Market, comprising 21 individual samples. These samples were tested for quality parameters including moisture content, salt content, ash content, total bacterial contamination, and Escherichia coli contamination. In addition, qualitative tests were conducted to detect the presence of formalin. If formalin was detected, quantitative analysis was subsequently performed. The test results showed that the moisture content of the samples ranged from 22.92% to 38.19% (SNI maximum limit: 40%), the salt content ranged from 12.59% to 13.94% (SNI standard: 12–20%), and the ash content ranged from 0.22% to 0.29% (SNI maximum limit: 0.3%). Total bacterial contamination and E. coli levels also complied with the SNI standards, with limits of 5×10⁵ colonies/gram and <3 MPN/gram, respectively. Formalin identification results revealed that one out of the 21 salted fish samples contained formalin, with a measured concentration of 15.35 ppm. Based on these findings, it can be concluded that the quality of salted fish sold at the Pemalang Morning Market, Central Java, generally complies with the SNI standards. However, one sample was confirmed to contain formalin.